A study on the Influence of Social Media and Collaborative Learning toward Learning Process among STML Students - Ang, Chin Siang; Noordin, Alminnourliza (Universiti Utara Malaysia, 2020)
Social media became a valuable of technology used in our daily life, especially for young generation, including students who are studying in UUM. Therefore, the objective of this study is to determine the relationship social media and collaborative learning towards learning process of School of Technology Management & Logistics (STML) students, as well as determine the purpose of using social media on learning process. This study adopts the quantitative survey method. The instrument consists of 40 items using the Likert scale. This study collected 302 data sets from STML. The regression results show that the social media and collaborative learning are significant determinants of learning process towards STML students. It is also found that social media and collaborative learning is positively related to the learning process and most of the STML students using social media for the purpose of learning process. These findings are supported by previous studies